Critical Medical Anthropology-Perspectives in and from Latin America (UCL Press, 2021)
Critical Medical Anthropology presents inspiring work from scholars doing and engaging with ethnographic research in or from Latin America, addressing themes that are central to contemporary Critical Medical Anthropology (CMA). This includes issues of inequality, embodiment of history, indigeneity, non-communicable diseases, gendered violence, migration, substance abuse, reproductive politics and judicialisation, as these relate to health